PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN SISWA PADA MASA PANDEMI DI MAN 3 MEDAN - T. Darmansah; Syarwan Hafidz Surbakti (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The Covid-19 virus has not only had a critical effect on the world of health, but also had a critical effect on the world of education. To prevent the Covid-19 outbreak, the government emphasizes staying at home and limiting all activities that endanger the community. Like keeping a distance, wearing a mask and so on. With the aim for the good health of the Indonesian people. But of course this epidemic has an impact on the world of education. However, this is where the principal's big role is in overcoming the problems that occurred when this epidemic emerged. The purposes of this study were to: 1. To determine the influence of the leadership of the Madrasah head during the pandemic at MAN 3 Medan, 2. To find out the learning system carried out by the Madrasah Head at MAN 3 Medan, 3. To find out how online learning works at MAN 3 Medan . The method used in this study is a quantitative research method by means of interviews and field observations. In this study, researchers used this method to facilitate the research process. In this study of the influence of the principal's leadership, it can be concluded that the principal plays an important role in handling learning during the Covid 19 pandemic in maintaining school accreditation and the quality of learning that occurs, especially in Man 3 Medan. The principal must also be able to optimize learning even though it is not face-to-face as usual, using performance that can really make students understand the material even though they are online..Principal Leadership, Improving the Quality of Student Learning